Baicalein benefits amyotrophic lateral sclerosis via reduction of Intraneuronal misfolded protein - Ting, Chen-Hung; Tai, Shao-Ting; Chang, Hsiang-Yu; Huang, Po-Ya; Cheng, Lo-Fan; Lai, Hsing-Jung; Kuo, Yih-Chih; Kao, Chia-Hsin; Wang, I-Fan; Tsai, Li-Kai (Biochimica et biophysica acta. General subjects, 2025)
Amyotrophic lateral sclerosis (ALS) is a rapidly progressive neurodegenerative disease characterized by muscle weakness and atrophy, with limited treatment options. The accumulation of misfolded proteins, such as misfolded superoxide dismutase 1 (mSOD1), contributes significantly to neuronal degeneration in ALS. Therapies targeting misfolded proteins represent a promising strategy. Baicalein, a flavonoid compound with neuroprotective properties, has shown efficacy in clearing misfolded proteins and improving behaviors in rodent models of Alzheimer's and Parkinson's diseases. However, its effects in ALS remain largely unexplored. This study demonstrated that baicalein treatment reduced total and misfolded SOD1 protein levels in both soluble and insoluble fractions of a motor neuron cell line overexpressing mutant SOD1. Baicalein also reduced intracellular SOD1 aggregates in cultured motor neurons transfected with SOD1/G93A, preserving neurite length. In an ALS mouse model expressing the SOD1/G93A transgene, baicalein treatment decreased mSOD1 aggregation, increased spinal motor neuron density, and reduced neuromuscular junction denervation. Furthermore, baicalein partially improved motor behaviors, as assessed by the rotarod test. These findings highlight baicalein's potential as a therapeutic agent for ALS, targeting intraneuronal misfolded proteins to ameliorate pathological changes and preserve motor function. •Baicalein lowered misfolded SOD1 protein levels in cultured motor neurons.•Baicalein reduced intracellular SOD1 aggregates in both cell and rodent models of ALS.•Baicalein improved neurite outgrowth in cultured neurons with a mutant SOD1 transgene.•Baicalein increased spinal motor neurons and decreased NMJ denervation in ALS mice.•Baicalein treatment improved motor behaviors in mice with ALS.